The Impact of Malaria on Liver Enzymes: A Retrospective Cohort Study (2010–2017). (16th May 2019) - Cheaveau, James; Marasinghe, Dewdunee; Akakpo, Samantha; Deardon, Rob; Naugler, Christopher; Chin, Alex; Pillai, Dylan R
Abstract: Background: It is unclear if malaria causes deranged liver enzymes. This has implications both in clinical practice and in research, particularly for antimalarial drug development. Method: We performed a retrospective cohort study of returning travelers (n = 4548) who underwent a malaria test and had enzymes measured within 31 days in Calgary, Canada, from 2010 to 2017. Odds ratios of having an abnormal alkaline phosphatase (ALP), alanine aminotransferases (ALT), aspartate aminotransferases (AST), and total bilirubin (TB) were calculated using multivariable longitudinal analysis with binomial response. Results: After adjusting for gender, age, and use of hepatotoxic medications, returning travelers testing positive for malaria had higher odds of having an abnormal TB (odds ratio [OR], 12.64; 95% confidence interval [CI], 6.32–25.29; P < .001) but not ALP (OR, 0.32; 95% CI, 0.09–1.10; P = .072), ALT (OR, 1.01; 95% CI, 0.54–1.89; P = .978) or AST (OR, 1.26; 95% CI, 0.22–7.37; P = .794), compared with those who tested negative. TB was most likely to be abnormal in the "early" period (day 0–day 3) but then normalized in subsequent intervals. Returning travelers with severe malaria (OR, 2.56; 95% CI, 0.99–6.62; P = .052) had borderline increased odds of having an abnormal TB, but malaria species (OR, 0.70; 95% CI, 0.24–2.05; P = .511) did not. Conclusions: In malaria-exposed returning travelers, the TB is abnormal, especially in the early period, but no abnormalities are seen for ALT, AST, or ALP.